Zarządzanie ryzykiem prawnym w przedsiębiorstwie - Kuziak, Katarzyna (Managing Legal Risk in an Enterprise Summary, 2008)
The purpose of this paper is to present sources and types of the legal risk for an enterprise and pay attention how to minimize this kind of risk. The concept "the legal risk management" is not clearly defined. The risk management may be understood as a process of measuring or assessing risk and than developing strategies to manage it. It means: transfer, avoidance, reduction (minimization), or acceptance of the risk. Consequences of the legal risk are financial losses and bad reputation. Finally the bad reputation of the enterprise may meet with a loss of clients and decrease value of the enterprise. Therefore the enterprise should pay attention to legal protection of the risk by organizing a good quality law department and financing it.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 91-99